1994
DOI: 10.1007/bf00996354
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomes (prosomes) inhibit the translation of Tobacco mosaic virus RNA by preventing the formation of initiation complexes

Abstract: Proteasomes (prosomes) are large multiprotein complexes. They are involved in protein degradation of ubiquitin-conjugated proteins and in the generation of MHC class I peptides. We gave further evidence that they interfere with in vitro protein synthesis. Proteasomes inhibit the translation of Tobacco mosaic virus RNA. Analysis of cell-free systems by sucrose gradient centrifugation revealed that they prevent the formation of 80S initiation complexes but not the early phase of initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…While no inhibition was observed with globin mRNA and cellular mRNAs of HeLa cells, the translation of TMV-RNA and mRNA isolated from adenovirusinfected HeLa cells was impeded (Horsch et al, 1989). Recent work of our laboratory indicates that proteasome prevents the formation of 80 S initiation complexes but not the early phase of initiation (Homma et al 1994). In addition, we have shown that proteasomes associated with tobacco mosaic virus RNA and poly(A) + mRNA from adenovirus-infected cells (Horsch et al, 1990).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…While no inhibition was observed with globin mRNA and cellular mRNAs of HeLa cells, the translation of TMV-RNA and mRNA isolated from adenovirusinfected HeLa cells was impeded (Horsch et al, 1989). Recent work of our laboratory indicates that proteasome prevents the formation of 80 S initiation complexes but not the early phase of initiation (Homma et al 1994). In addition, we have shown that proteasomes associated with tobacco mosaic virus RNA and poly(A) + mRNA from adenovirus-infected cells (Horsch et al, 1990).…”
mentioning
confidence: 67%
“…Interestingly, the in vitro synthesis of mRNA from adenovirus-infected HeLa cells and the translation of polycistronic TMV-RNA was impeded in the presence of proteasomes, while translation of HeLa mRNA and globin mRNA was not affected under the same conditions (Horsch et al, 1989;Homma et al, 1994). In addition very recent work of our laboratory has shown that translation of TMV-RNA was very sensitive to catalytic amounts of proteasomes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, the proteasome can interfere with the translation of viral RNA and mRNA in virus-infected cells (3,5,8,14,16,22). Ballut et al.…”
mentioning
confidence: 99%